IMPLEMENTATION OF COMMUNITY BASED SOCIAL MARKETING IN THE PROGRAM FOR INCREASING DISABILITY AWARENESS BY KOMUNITAS PEDULI INKLUSI NUSANTARA IN BLITAR - Nasution, Dian Eka Pratiwi; Setianingrum, S.Sos., M.A, Vinda Maya (The Commercium, 2022)
This study aims to determine the process of implementing a community-based social marketing campaign orCommunity Based Social Marketing, namely the Disability Awareness Improvement campaign in the Children'sLiteracy Movement (CLM) program carried out by Komunitas Peduli Inklusi Nusantara (KOPINUS) in Blitar and seethe changes felt by the community target.. The Children's Literacy Movement Program (CLM) is a learning assistanceprogram that applies inclusive education and an inclusive environment in its implementation and aims to provide aknowledge and experience related to the world of disability. So that participants can get to know the world ofdisabilities more deeply and eliminate negative views of people with disabilities. This research uses a qualitativeapproach with a case study method. Data collection was carried out through observation and interviews with partiesinvolved in the Children's Literacy Movement (CLM) program. The results showed that the Komunitas Peduli InklusiNusantara (KOPINUS) has implemented social marketing steps in the concept of community based social marketing.The campaign process will be maximized if every planning is done in more detail. Furthermore, the Children's LiteracyMovement (CLM) program received a positive response from the target community and there were differences in theperceptions and behaviors of the participants before joining the Children's Literacy Movement (CLM) program andafter participating in the program.Keywords: Disability Awareness, Disability, Inclusive Education, Social Marketing, Community, Community BasedSocial Marketing